Innovation and economic development the impact of information and communication technologies in Latin America - Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2010)
Information and communication technologies (ICT) are spreading fast across Latin America and the Caribbean. This trend has brought about important economic and social changes, which have largely gone unmeasured until recently. Here, analysts from the United Nations Economic Commission for Latin America and the Caribbean along with other distinguished scholars in the field of ICT, growth and productivity provide theoretical and empirical insights to the debate on the role of ICT in economic development.
1. Latin America and the world economy / Dale W. Jorgenson and Khuong Minh Vu -- 2. Technical change and economic growth : some lessons from secular patterns and some conjectures on the current impact of ICT / Carolina Castaldi and Giovanni Dosi -- 3. ICT and productivity growth in Europe : an update and comparison with the US / Mary O'Mahony, Marcel Timmer and Bart van Ark -- 4. ICT investment in Latin America : does it matter for economic growth? / Gaaitzen J. De Vries ... [et al.] -- 5. Growth, productivity and information and communications technologies in Latin America, 1950-2005 / Claudio Aravena ... [et al.] -- 6. The impact of information and communication technologies on economic growth in Latin America in comparative perspective / Nauro F. Campos -- 7. ICT, learning and growth : an evolutionary perspective / Mario Cimoli and Nelson Correa -- 8. ICT and knowledge complementarities : a factor analysis on growth / Marco Capasso and Nelson Correa -- 9. A dynamic input-output simulation analysis of the impact of ICT diffusion in the Brazilian economy / Fabio Freitas, David Kupfer and Esther Dweck -- 10. The relative impact of the regulatory framework on the diffusion of ICT : evidence from Latin America, 1989-2004 / Nauro F. Campos.
Includes bibliographical references and index.
Keywords: Technological innovations -- Economic aspects; Economic development; Electronic books